RE-OS AGES FOR THE SHAMEIKA PORPHYRY MO DEPOSIT AND THE LIPOVY LOG RARE METAL PEGMATITE, CENTRAL URALS, RUSSIA - Mao J.; Yu J.; Du A.; Seltmann R. (My University, 2003)
The ages for pegmatite rare metal and beryl (emerald) deposits, as well as porphyry Mo deposits in the Hercynian Uralide orogen, are not well known. Five molybdenite samples from the Lipovy Log pegmatite Ta-Nb-Mo deposit and 11 molybdenite samples from the Shameika porphyry Mo deposit were selected for Re-Os dating. Both mineral occurrences are spatial-temporally associated with the Adui composite granite pluton, a well-known rare metal-related granite intrusion. A Re-Os isochron age of 262.0+-7.3 Ma was obtained for the Lipovy Log pegmatite Ta-Nb-Mo deposit. The Shameika porphyry Mo deposit, associated with the Malyshevo leucogranitic stock and surrounding hornfels, provided isochron ages of 273Ǉ and 282ǈ Ma, for two groups of molybdenite (within stock and within hornfels). All of these Re-Os ages are consistent with presumed Hercynian ages for the granite intrusions, formed in a post-collisional setting within the Uralide orogen.